Answer:
6
Step-by-step explanation:
(g × f)(x) = g(x) × f(x) = x²(- x + 5)
To evaluate (g × f)(- 1) substitute x = - 1 into the product
x²(- x + 5)
= (- 1)²(- (- 1) + 5)
= 1(1 + 5)
= 1 × 6 = 6
Answer:
no you cant
Step-by-step explanation:
9514 1404 393
Answer:
D. a ║ b
Step-by-step explanation:
If we figure the other angle of each linear pair, we can directly compare angles to see if corresponding angles are the same. Where they are the same, the lines are parallel.
Line a is parallel to line b.